Our Lives Before the Law : Constructing a Feminist Jurisprudence - Baer, Judith A. (Book collections on Project MUSE., 1999)
According to Judith Baer, feminist legal scholarship today does not effectively address the harsh realities of women's lives. Feminists have marginalized themselves, she argues, by withdrawing from mainstream intellectual discourse. In Our Lives Before the Law, Baer thus presents the framework for a new feminist jurisprudence--one that would return feminism to relevance by connecting it in fresh and creative ways with liberalism. Baer starts from the traditional feminist premise that the legal system has a male bias and must do more to help women combat violence and overcome political, economic.